PLC–SCADA Based Control of Booster Pumps with Alternating Operation and PID Regulation - Viet-Truong Nguyen; Anh-Son Hoang; Van-Dong-Hai Nguyen; Thi-Quynh-Huong Hoang; Ho-Anh-Vu Ho; Tan-Tai Tran; Mai-Bao Trung; Le-Cong-Vinh Nguyen; Thi-Thuy-Duong Do; Binh-Hau Nguyen; Le-Phuc-Khuong Nguyen; Duc-Hieu Nguyen; Duy-Thinh Le (Peneliti Teknologi Teknik Indonesia, 2025)
In the current context, the demand for clean water in daily life and in industrial environments is increasing, showing that the need for improved operation of water supply systems as well as management efficiency is essential. The pressure pump system is one of the important factors that help improve the stability of the water supply demand. The system helps ensure the quality of the water supply, has the function of maintaining stable pressure in the pipeline, avoiding sudden pressure changes that damage equipment, causing unsafe incidents at the operating site, and for users. This paper presents an experimental study on a booster pump system model integrated with programmable logic controller (PLC) and supervisory control and data acquisition (SCADA) technologies, along with a human-machine interface (HMI), to automate operation, alternate pump operation, apply proportional integral derivative (PID) control without an expansion tank, and monitor the system without manual or semi-automatic intervention. Based on the experiment and evaluation methods, the study shows the potential for improving the pressure pump system in the wastewater treatment and domestic water supply industry.